Formation and Persistence of Procoagulant and Fibrinolytic Activities in Circulation after Strenuous Physical Exercise - Hansen, John-Bjarne; Wilsgård, Line; Olsen, Jan Ole; Østerud, Bjarne (Thrombosis and Haemostasis, 1990)
Seven healthy male volunteers were subjected to exercise of short (STR; 1.7 km), middle (MTR; 4.8 km) and long (LTR; 10.5 km) term runs at a speed close to maximal capacity. Blood samples were drawnbefore, immediately after exercise and at intervals over the next 10 h. FVTIIR: Ag (von Willebrand factor) rose 2.2–3.2 fold and persisted at higher levels than baseline during the observation time. A spontaneous drop in FVII (p <0.03) was found immediately after STR(13.5 ± 2.5%) and LTR (18.3 ± 2.4%), whereas only a minor decrease (7.5 ± 6.5%) occurred in MTR. The procoagulant activity of monocytesisolated from whole blood exposed to LPS showed a striking enhancement in STR and MTR. An immediate enhancement in fibrinolytic activity was found in all groups (p <0.03) assessed by increased plasma levels of t-PA and shortened whole blood clot lysis time (WBCLT). The transient shortening of WBCLT was succeeded by a tendency to prolongation of the lysis time. A 45-year old male differed markedly from the others by demonstrating an extreme and consistent prolongation of WBCLT. Thus, it hasbeen speculated that strenuous exercise possibly makes a subject more susceptible to a thrombotic event.